Assessment of Radiological Significance of the Wastes Generated from the Triple Super Phosphate (TSP) Fertilizer Factory, Chittagong, Bangladesh (Journal of Bangladesh Academy of Sciences, 2012)
The activity concentration of 226Ra, 232Th and 40K was determined in solid and liquid samples collected from the TSP Fertilizer Factory, Chittagong, Bangladesh. A total of 18 samples of seven different kinds (including liquid and solid wastes) were collected and analyzed by gamma ray spectrometry technique using a high purity germanium (HPGe) detector of 40% relative efficiency. The analysis of the liquid waste samples showed that the average activity concentrations of 226Ra and 232Th were 6.26 ± 0.63 and 10.01 ± 1.39 Bq/L, respectively and no 40K was detected in any of the liquid samples. In the solid waste samples the average value of activity concentrations of 226Ra, 232Th and 40K were 187.49 ± 4.88, 70.06 ± 11.76 and 655.94 ± 110.24 Bq/kg, respectively. Considering the stored wastes as a part of the ambient environment of the factory, radium equivalent activity, radiation hazard index and external annual effective dose to the worker and public due to these wastes were also calculated and compared with world average values. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10923 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 79-88, 2012